2015
DOI: 10.1186/s12885-015-1913-6
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1, BRCA2 and PALB2 mutations and CHEK2 c.1100delC in different South African ethnic groups diagnosed with premenopausal and/or triple negative breast cancer

Abstract: BackgroundCurrent knowledge of the aetiology of hereditary breast cancer in the four main South African population groups (black, coloured, Indian and white) is limited. Risk assessments in the black, coloured and Indian population groups are challenging because of restricted information regarding the underlying genetic contributions to inherited breast cancer in these populations. We focused this study on premenopausal patients (diagnosed with breast cancer before the age of 50; n = 78) and triple negative br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…Note that only 11 published studies were found that included male BRCA1/2 PSV carriers, but no additional BRCA1/2 PSVs were identified from these reports. Forty‐eight studies were included in the present report: 16 studies of Sub‐Saharan Africans (Awadelkarim et al, ; Biunno et al, ; Diez et al, ; Elimam et al, ; Fackenthal et al, ; Fackenthal et al, ; Francies et al, ; Gao et al, ; Luyeye Mvila et al, ; Stoppa‐Lyonnet et al, ; van der Merwe et al, ; Zhang et al, ; Zhang et al, ; Zhang, Fackenthal, Huo, Zheng, & Olopade, ; Zheng et al, ; Zoure et al, ), 27 of African Americas (Arena et al, ; Arena et al, ; Arena et al, ; Castilla et al, ; Churpek et al, ; Dangel et al, ; Futreal et al, ; Ganguly, Dhulipala, Godmilow, & Ganguly, ; Q. Gao, Neuhausen, Cummings, Luce, & Olopade, ; Q. Gao, Sveen, Cummings, & Olopde, ; Q. Gao et al, ; Gayol et al, ; Haffty et al, ; Hall et al, ; John et al, ; Kanaan et al, ; Kedar‐Barnes et al, ; Lynce et al, ; Martin et al, ; Miki et al, ; Nanda et al, ; Olopade et al, ; Pal et al, ; Pal et al, ; Pal, Permuth‐Wey, Holtje, & Sutphen, ; Panguluri et al, ; Shen et al, ; Sutphen & Ferlita, ; Whitfield‐Broome, Dunston, & Brody, ), and three of Afro‐Caribbean populations (Akbari et al, ; Donenberg et al, ; Donenberg et al, ) and one study reporting SRAA of unspecified geography (Hall et al, ). From these papers, we identified 414 BRCA1 and 187 BRCA2 PSVs, and 108 unique BRCA1 and 103 unique BRCA2 PSVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that only 11 published studies were found that included male BRCA1/2 PSV carriers, but no additional BRCA1/2 PSVs were identified from these reports. Forty‐eight studies were included in the present report: 16 studies of Sub‐Saharan Africans (Awadelkarim et al, ; Biunno et al, ; Diez et al, ; Elimam et al, ; Fackenthal et al, ; Fackenthal et al, ; Francies et al, ; Gao et al, ; Luyeye Mvila et al, ; Stoppa‐Lyonnet et al, ; van der Merwe et al, ; Zhang et al, ; Zhang et al, ; Zhang, Fackenthal, Huo, Zheng, & Olopade, ; Zheng et al, ; Zoure et al, ), 27 of African Americas (Arena et al, ; Arena et al, ; Arena et al, ; Castilla et al, ; Churpek et al, ; Dangel et al, ; Futreal et al, ; Ganguly, Dhulipala, Godmilow, & Ganguly, ; Q. Gao, Neuhausen, Cummings, Luce, & Olopade, ; Q. Gao, Sveen, Cummings, & Olopde, ; Q. Gao et al, ; Gayol et al, ; Haffty et al, ; Hall et al, ; John et al, ; Kanaan et al, ; Kedar‐Barnes et al, ; Lynce et al, ; Martin et al, ; Miki et al, ; Nanda et al, ; Olopade et al, ; Pal et al, ; Pal et al, ; Pal, Permuth‐Wey, Holtje, & Sutphen, ; Panguluri et al, ; Shen et al, ; Sutphen & Ferlita, ; Whitfield‐Broome, Dunston, & Brody, ), and three of Afro‐Caribbean populations (Akbari et al, ; Donenberg et al, ; Donenberg et al, ) and one study reporting SRAA of unspecified geography (Hall et al, ). From these papers, we identified 414 BRCA1 and 187 BRCA2 PSVs, and 108 unique BRCA1 and 103 unique BRCA2 PSVs.…”
Section: Resultsmentioning
confidence: 99%
“…Note that only 11 published studies were found that included male BRCA1/ 2 PSV carriers, but no additional BRCA1/2 PSVs were identified from these reports. Forty-eight studies were included in the present report: 16 studies of Sub-Saharan Africans (Awadelkarim et al, 2007;Biunno et al, 2014;Diez et al, 2011;Elimam et al, 2017;Fackenthal et al, 2005;Fackenthal et al, 2012;Francies et al, 2015;Gao et al, 2000;Luyeye Mvila et al, 2014;Stoppa-Lyonnet et al, 1997;van der Merwe et al, 2012;Zhang et al, 2009;Zhang et al, 2012;Zhang, Fackenthal, Huo, Zheng, & Olopade, 2010;Zheng et al, 2018;Zoure et al, 2018), 27 of African Americas (Arena et al, 1996);Arena et al, 1997;Arena et al, 1998;Castilla et al, 1994;Churpek et al, 2015;Dangel et al, 1999;Futreal et al, 1994;Ganguly, Dhulipala, Godmilow, & Ganguly, 1998;Q. Gao, Neuhausen, Cummings, Luce, & Olopade, 1997;Q.…”
Section: African Ancestry Individuals With Brca1/2 Pathogenic Sequementioning
confidence: 99%
“…6448dupTAc. 7934delGFounder-c.5946delTC.8162delGSchoeman M, et al 2013 [58]c.5999del4c.6174delTc.582G > AFrancies FZ, et al 2015 [59]c.5771_5774delTTCAc.5213_5216delCTTAc.8754 + 1G > Ac.9097_9098insAc.4798_4800delAATc.7712A > Gc.9875C > Tc.7934delG founderfounderAfrikaner population of South Africa Seymour HJ, et al2016 [60]c.6621delASouth Africac.6761_6762delTTc.5073dupAMoroccoLAARABI FZ, et al2011 [61]c.3381delT Tazzite A, et al 2012 [62]c.7110delAc.7235insGc.517-1G > Ac.6428 C > A Guaoua S, et al2014 [63]c.745-1G > A Jouhadi H, et al2016 [64]c.5682insATunisia Troudi W, et al 2007 [65]c.1309del4c.-25G > Ac.6301 A > Cc.1595 A > Tc.7242 A > Gc.865 A > Gc.1310_1313del (1538delAAGA) Fourati A, et al 2014 [66]c.-26G > A …”
Section: Discussionmentioning
confidence: 99%
“…These two subtypes are known to present a clinically aggressive phenotype, including resistance to treatment and high rates of disease recurrence (7)(8)(9). Although the determinants for the high prevalence of these unfavorable tumor subtypes is unclear, several studies implicate intrinsic genetic differences, such as the presence of founder mutations in breast cancer susceptibility genes, including the BRCA1 gene (10)(11)(12) or unknown genomic variants identified by genomic wide association studies (13)(14)(15)(16).…”
Section: Patterns Of Copy Number Alterations In Primary Breastmentioning
confidence: 99%
“…Among the African countries, SA has the highest number of published genomic research studies (assessed between 2004-2013), however only 6.1% of these studies are associated with cancer (20). To the best of our knowledge, few breast cancer studies have characterized patient genomic profiles and/or specific molecular alterations in their populations (14,(21)(22)(23)(24)(25). As a consequence, there is limited knowledge on their tumor biology and the corresponding lack of clinically relevant biomarkers that would be particularly beneficial for the prognosis and treatment of patients with breast cancer representative of the diverse racial groups of SA.…”
Section: Patterns Of Copy Number Alterations In Primary Breastmentioning
confidence: 99%